Hardware hacking : have fun while voiding your warranty - Grand, Joe; Russell, Ryan, 1969- (Syngress Pub., 2004)
"If I had this book 10 years ago, the FBI would never have found me!"--Kevin Mitnick This book has something for everyone---from the beginner hobbyist with no electronics or coding experience to the self-proclaimed "gadget geek." Take an ordinary piece of equipment and turn it into a personal work of art. Build upon an existing idea to create something better. Have fun while voiding your warranty! Some of the hardware hacks in this book include: * Don't toss your iPod away when the battery dies! Don't pay Apple the $99 to replace it! Install a new iPod battery yourself without Apple's "help" * An Apple a day! Modify a standard Apple USB Mouse into a glowing UFO Mouse or build a FireWire terabyte hard drive and custom case * Have you played Atari today? Create an arcade-style Atari 5200 paddle controller for your favorite retro videogames or transform the Atari 2600 joystick into one that can be used by left-handed players * Modern game systems, too! Hack your PlayStation 2 to boot code from the memory card or modify your PlayStation 2 for homebrew game development * Videophiles unite! Design, build, and configure your own Windows- or Linux-based Home Theater PC * Ride the airwaves! Modify a wireless PCMCIA NIC to include an external antenna connector or load Linux onto your Access Point * Stick it to The Man! Remove the proprietary barcode encoding from your CueCat and turn it into a regular barcode reader * Hack your Palm! Upgrade the available RAM on your Palm m505 from 8MB to 16MB Includes hacks of today's most popular gaming systems like Xbox and PS/2. Teaches readers to unlock the full entertainment potential of their desktop PC. Frees iMac owners to enhance the features they love and get rid of the ones they hate